Utlenianie jonu manganawego tlenem powietrza - Kołaczkowski, Stanisław T.; Zgoła, Lidia (Zielona Góra: Uniwersytet Zielonogórski)
The proces of Mn2+ oxygenation with air oxygen has been investigated in the pH range form 0,0 to 12,5. The beginning of this process is stated by pH = 2,2, 50% Mn'' is oxydized by pH = 7,0, and 100% by NaOH added in a stoichiometric quantity to full precipitation of Mn(OH)2. This fact can prove the hypothesis, the oxygenation ot Mn'' with air is a topochemical one, namely an oxidation of Mn''(OH)2 and not of the manganese (II) ion - Mn2+.
Keywords: jon manganawy; utlenianie